Wavering between life and death: a qualitative study into the perceived causes and needs of persons with persistent suicidality - Palm, Mette; van Veen, Sisco; Schweren, Lizanne; Beekman, Aartjan; van Wijngaarden, Els; Elzinga, Elke (Frontiers in Psychiatry, 2025)
BackgroundOne of the key issues in the current knowledge base on persistent or chronic suicidality is the discrepancy between the extensive experiential knowledge embedded in clinical practice and its limited representation in the scientific literature. Both individuals living with persistent suicidality and the professionals who support them develop beliefs about its underlying causes and what is needed for effective management or treatment. Studying these subjective understandings may provide valuable insights into the contextual, relational and psychological factors related to persistent suicidality and help inform appropriate care strategies.AimsThis study aims to identify the perceived causes of persistent suicidality and the needs of those affected, from both the perspectives of individuals with lived experience of persistent suicidality and professionals providing support.MethodSemi-structured interviews were conducted with 12 individuals with lived experience of persistent suicidality and 10 occupational experts. Data were analyzed using reflexive thematic analysis.ResultsAlthough individual experiences vary, persistent suicidality is perceived to be linked to childhood trauma and psychopathology. It may persist due to its perceived functionality or as a result of unsuccessful treatment and resulting feelings of demoralization. Key needs include continuity in care relationships, feeling genuinely heard, and openly discussing suicidal thoughts. This involves acceptance of these thoughts and exploring their meaning. Some individuals with persistent suicidality perceive aspects of care as ineffective or, in some cases, as contributing to further distress.ConclusionsCare for individuals with persistent suicidality should not focus solely on recovery but also on the acceptance and managing of suicidal thoughts. Effective care strategies may include teaching alternative coping and communication methods. The findings underscore the need for continuity of care and emphasize the importance of addressing non-disclosure and transference-countertransference dynamics in therapy.